THEORY AND METHOD OF DESIGN IN THE CONTEXT O F DEVELOPMENT OF MODEM NATIONAL DESIGN - Antonovych, Ye. (Pedagogy of Higher and Secondary Education, 2022)
Theory and method of design in the context of development of modem national design. Problems and tasks in domain of development of leading elaboration directions of modem Ukrainian design and designer education are examined in the article.